KINERJA PEGAWAI DALAM PELAYANAN PEMBATALAN HAJI DI MASA PANDEMI COVID-19 PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI RIAU - Mastanah Mastanah (Jurusan Manajemen Dakwah, Fakultas Ilmu Dakwah dan Ilmu Komunikasi, UIN Syarif Hidayatulla, 2022)
This study aims to determine the performance of employees in Hajj Cancellation Services during the Covid-19 Pandemic at the Regional Office of the Ministry of Religion of Riau Province. Riau. The study uses a qualitative approach, which carries out a research process that will create descriptive data in the form of writing from various sources, namely the Regional Office of the Ministry of Religion of Riau Province. The data collection technique is by observation, in the sense that the author examines directly the Regional Office of the Ministry of Religion of Riau Province, conducts interviews with employees who are authorized to cancel Hajj, such as the Head of the Hajj Registration and Documents Section, the Head of the Hajj and Umrah Organization (PHU), employees, and read the documents and information available on the website. From the results of this study, it was shown and explained that the performance of the employees of the Regional Office of the Ministry of Religion of Riau Province in the service of canceling the registration of prospective pilgrims had Standard Operating Procedures applied.